TRANSFORMASI KONSEPTUAL MASYARAKAT KONTEMPORER: DIALEKTIKA NEOMODERNISME DAN POSTMODERNISME TERHADAP RASIONALITAS DAN EMANSIPASI SOSIAL DI ERA DIGITAL - Aisyah Nur; Devina Novela; Rahma Dona; Mei Arina Ilmi AS (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to philosophically examine the crisis of rationality and the challenges of social emancipation in the digital society through a dialectical approach between neomodernism and postmodernism. Against the backdrop of the growing dominance of instrumental rationality in digital ecosystems which marginalizes ethical, reflective, and participatory dimensions this study explores two major schools of contemporary social philosophy. Neomodernism, through Jürgen Habermas' theory of communicative rationality, emphasizes rational discourse and consensus as the basis for a just social order. In contrast, postmodernism, as represented by Michel Foucault and Jean-François Lyotard, rejects universalist claims and deconstructs the role of power in the production of truth and representation. Employing a qualitative-philosophical method and philosophical discourse analysis, this research engages with primary texts from key thinkers as well as secondary literature on algorithmic technology, digital democracy, and global structural inequalities. The findings reveal that while normative neomodernist and postmodern deconstructive approaches are each insightful, neither alone is sufficient to address the complexity of contemporary crises. Accordingly, the study proposes a dialectical synthesis: a model of dialogical-pluralistic emancipation that integrates communicative ethics with the recognition of narrative particularity to form a more reflective, contextual, and transformative mode of social critique.